Co-infection of H9N2 Influenza A Virus and Escherichia coli in a BALB/c Mouse Model Aggravates Lung Injury by Synergistic Effects - Wang, Song; Jiang, Ning; Shi, Wenhao; Yin, Hang; Chi, Xiaojuan; Xie, Yanhui; Hu, Jingyun; Zhang, Yanwei; Li, Huangping; Chen, Ji-Long (Frontiers in Microbiology, 2021)
Pathogens that cause respiratory diseases in poultry are highly diversified, and co-infections with multiple pathogens are prevalent. The H9N2 strain of avian influenza virus (AIV) and Escherichia coli (E. coli) are common poultry pathogens that limit the development of the poultry industry. This study aimed to clarify the interaction between these two pathogens and their pathogenic mechanism using a mouse model. Co-infection with H9N2 AIV and E. coli significantly increased the mortality rate of mice compared to single viral or bacterial infections. It also led to the development of more severe lung lesions compared to single viral or bacterial infections. Co-infection further causes a storm of cytokines, which aggravates the host’s disease by dysregulating the JAK/STAT/SOCS and ERK1/2 pathways. Moreover, co-infection mutually benefited the virus and the bacteria by increasing their pathogen loads. Importantly, nitric oxide synthase 2 (NOS2) expression was also significantly enhanced by the co-infection. It played a key role in the rapid proliferation of E. coli in the presence of the co-infecting H9N2 virus. Therefore, our study underscores the role of NOS2 as a determinant for bacteria growth and illustrates its importance as an additional mechanism that enhances influenza virus-bacteria synergy. It further provides a scientific basis for investigating the synergistic infection mechanism between viruses and bacteria.